Production of Naturally γ-Aminobutyric Acid-Enriched Cheese Using the Dairy Strains Streptococcus thermophilus 84C and Lactobacillus brevis DSM 32386 - Carafa, Ilaria; Stocco, Giorgia; Nardin, Tiziana; Larcher, Roberto; Bittante, Giovanni; Tuohy, Kieran; Franciosi, Elena (Frontiers in Microbiology, 2019)
The cheese-derived strains Streptococcus thermophilus 84C isolated from Nostrano cheese, and Lactobacillus brevis DSM 32386 isolated from Traditional Mountain Malga cheese have been previously reported as γ-aminobutyric acid (GABA)-producers in vitro. In the present study, the ability of these strains to produce GABA was studied in experimental raw milk cheeses, with the aim to investigate the effect of the culture and the ripening time on the GABA concentration. The cultures used consisted on S. thermophilus 84C alone (84C) or in combination with L. brevis DSM 32386 (84C-DSM). The control culture was a commercial S. thermophilus strain, which was tested alone (CTRL) or in combination with the L. brevis DSM 32386 (CTRL-DSM). The pH evolution, microbiological counts, MiSeq Illumina and UHPLC-HQOMS analysis on milk and cheese samples were performed after 2, 9 and 20 days ripening. During the whole ripening, the pH was always under 5.5 in all batches. The concentration of GABA increased during ripening, with the highest content in 84C after 9 days ripening (84 ± 37 mg/kg), in 84C-DSM and CTRL-DSM after 20 days ripening (91 ± 28 and 88 ± 24 mg/kg, respectively). The data obtained support the hypothesis that S. thermophilus 84C and L. brevis DSM 32386 could be exploited as functional cultures, improving the in situ bio-synthesis of GABA during cheese ripening.